PENGARUH KEPUASAN PADA LOYALITAS YANG DIMODERASI OLEH KEYAKINAN - DANAS AVIANTO NUGROHO (Riset Manajemen dan Akuntansi, 2016)
Customer loyalty is the main issue of this study. In this context, loyalty is allegedly providing long-term profitability for the company. Therefore, marketers need to understand the factors that affect customer loyalty. Regarding that condition, this study constructs a model of loyalty that is expected to explain the phenomenon of customer loyalty in the seed brand Multi Global Agrindo. From the model is constructed, based on the problems that arise are the following (1) Perceptions of product quality directly affect on customer satisfaction. (2) Perceptions of service quality directly affect on customer satisfaction. (3) Certainty moderate the direct affect of perceptions of product quality on customer satisfaction. (4) Certainty moderate the direct affect of perceptions of service quality on customer satisfaction. (5) Satisfaction direct effect on customer loyalty. (6) Certainty moderate the direct affect of satisfaction on customer loyalty. In this study, the sample consisted of 250 respondents who intend to loyal to use the seed brand Multi Global Agrindo. Convenience sampling is a sampling technique chosen. Data analysis using Structural Equation Modeling (SEM). The results of this study suggest that customer loyalty can built by marketers by increasing costumer satisfaction. Satisfaction can be formed by increasing the perception of service quality and perceptions of product quality. Stimulus needed to build the perception of service quality is increase the dimensions of reliability, assurance, responsiveness, empathy, and tangible of service. While the stimulus needed to build the perception of the quality of the product is improve product quality to resist pests and diseases, defenseless wide adaptability, high productivity and yield acceptable fruit by merchant. Another thing that marketers need to know, certainty has no moderating effect on customer satisfaction and loyalty. Keyword : perceived product quality, perceived service quality, satisfaction, certainty, loyalty